MENAKAR PENEGAKAN HAK ASASI MANUSIA DI INDONESIA: HASIL SURVEI SKALA LOKAL SAMPAI GLOBAL - Subekti, Slamet (HUMANIKA, 2014)
Abstract This paper discusses human rights in Indonesia today is based on the results of the locally, nationally and globally surveys. The national and international surveys concluded that the enforcement of human rights in Indonesia in 2013 decreased due to the performance of the institutions of human rights is not optimal, and that the government failed to crack down on violations of human rights. Meanwhile, the survey among students shows positive response to the exercise of the right human rights in civil and political; economic, social and cultural; and solidarity dimensions. The importance of human rights education is to support the development of student character with Indonesian personality, and responsive to the global environment. Keywords: Human Rights in Indonesia, local, national and global survey